Effect on Irradiance of the eruption of the Cordon Caulle (Chile) at different altitudes in the Nahuel Huapi National Park (Patagonia, Argentina) - Diaz, Susana Beatriz (2013)
Volcanic eruptions inject ash and non-ash particles into the atmosphere, modifying regional Aerosols Optical Depth (AOD) and aerosols size distribution, which affect irradiance at the earth’s surface. In this paper, we analyze the effect of the eruption of Puyehue-Cordon Caulle (Chile) on irradiance in the area of the Nahuel Huapi National Park (NHNP) (~100 km southeast of Puyehue-Cordon Caulle), at different altitudes. In this paper we only included the results for direct and AOD obtained during field campaigns at two consecutive years, before and after the eruption. Three days presented clear skies during most of the day in 2011. Two of those days, showed AOD similar to the values in 2010. On the third days, at the lowest altitude site (804m.s.l.), AOD were near 200% larger than in 2010. The largest decreases observed, at noon, in the direct irradiance was ~30% at 380 nm and 25% at 500nm, increasing with Solar Zenith Angle (SZA). The effect was less pronounced at the site at highest altitude (1930 m.s.l.), where the AODs increase was near 90% and the direct noon irradiance decrease 10% at 380 nm and 7% at 500nm. © (2013) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE). Downloading of the abstract is permitted for personal use only.